0.008(3-k)+0.05(k-6)=1

Simple and best practice solution for 0.008(3-k)+0.05(k-6)=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.008(3-k)+0.05(k-6)=1 equation:


Simplifying
0.008(3 + -1k) + 0.05(k + -6) = 1
(3 * 0.008 + -1k * 0.008) + 0.05(k + -6) = 1
(0.024 + -0.008k) + 0.05(k + -6) = 1

Reorder the terms:
0.024 + -0.008k + 0.05(-6 + k) = 1
0.024 + -0.008k + (-6 * 0.05 + k * 0.05) = 1
0.024 + -0.008k + (-0.3 + 0.05k) = 1

Reorder the terms:
0.024 + -0.3 + -0.008k + 0.05k = 1

Combine like terms: 0.024 + -0.3 = -0.276
-0.276 + -0.008k + 0.05k = 1

Combine like terms: -0.008k + 0.05k = 0.042k
-0.276 + 0.042k = 1

Solving
-0.276 + 0.042k = 1

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '0.276' to each side of the equation.
-0.276 + 0.276 + 0.042k = 1 + 0.276

Combine like terms: -0.276 + 0.276 = 0.000
0.000 + 0.042k = 1 + 0.276
0.042k = 1 + 0.276

Combine like terms: 1 + 0.276 = 1.276
0.042k = 1.276

Divide each side by '0.042'.
k = 30.38095238

Simplifying
k = 30.38095238

See similar equations:

| g(x)=2x+1(x+4)2x+12 | | (3xy+1)(2xy-3)= | | 12-4x=-15+2x | | x^6=1296 | | 5y-8x=8x | | f(x)=x+4(2x+1)8x^2+4 | | 4-6(2x-3)+1=3+7(5-x) | | 2-8m=14-3+8m | | t^2-24=2t | | k^2-20k-35=0 | | g(x)=x+7(2x)2x+14 | | 11/18x^2-7x-56=0 | | 0.6111x^2-7x-56=0 | | 4(x+2)=3(2x-(6-x)) | | 35x+12=4x+3 | | f(x)=2x(x+7)2x^2+14 | | 30=(5/9)(F-32) | | 30(9/5) | | x=(3)(3)(3) | | (6x+7)(2x+1)= | | 5n^2+13n-28=0 | | -4.9t^2+10t+2=0 | | 8-9p=1 | | 15a^2-22a-5=0 | | (3a+2)(a-2)= | | (-3)-(-10)= | | ((-7)-3)((-3)-(10))= | | x/5-x/10=3 | | 2x^4-6x^3+x^2+3=0 | | 13(2-x)=7(x+8) | | 5x+3x^2=25 | | c/a-p/a=1 |

Equations solver categories